The Role of Post Quantity, Views, and Reviews in Enhancing User-Generated Content and Stimulating Purchase Intention - Theresia Setiawan, Naomi; Sri Darma, Gede (Journal Research of Social Science, Economics, and Management, 2025)
This study investigates how the quantity of posts, views, and reviews (KPVR) affects the perceived source credibility and information usefulness of User-Generated Content (UGC), and subsequently how these perceptions influence consumer attitudes and online purchase intention for cosmetic products. Grounded in the Theory of Planned Behavior (TPB), this quantitative research was conducted in Denpasar, Indonesia, targeting female consumers who have engaged with UGC on TikTok and YouTube. A total of 115 valid responses were collected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results reveal that KPVR significantly enhances both source credibility and information usefulness. These, in turn, positively influence consumer attitudes and ultimately strengthen purchase intentions. This study highlights the vital role of digital interaction metrics in shaping consumer decision-making, offering both theoretical and managerial implications